SISTEM PAKAR DIAGNOSIS PENYAKIT KULIT PADA KUCING BERBASISI WEB DENGAN METODE FORWARD CHAINING - Adriana, Lia; Handoko, Koko (LPPM Universitas Putera Batam, 2021)
One of the most popular pets to keep is a cat. Cats are one of the animals that are kept by the community because they can be good friends for humans. To help the general public, especially cat keepers whose knowledge is still lacking in recognizing the types of skin diseases in cats and save time and costs in solving problems by using a system expert. An expert system that will be used to diagnose skin diseases in cats, as well as provide ways to prevent and overcome them using the forward chaining method. Forward Chaining is an information-driven (data-driven) approach. In this approach, the search begins with input data, and then attempts to describe conclusions. Forward tracking looks for facts that match the IF part of the IF-THEN condition. then the rule is stimulated and the next rule is tested. The results of this study are a system that can diagnose skin diseases in cats based on a website. With the existence of an expert system for diagnosing skin diseases in cats, it can help the general public, especially cat keepers, to find out earlier about the types of skin diseases in cats and the symptoms of these skin diseases. and handling solutions.